A constituição da subjetividade docente: o confronto entre as políticas de formação de professores e as possíveis influências do neoliberalismo - Toniol, Lucas Cardoso (Universidade Federal de São Carlos, 2019)
Teacher training is an important area of ​​education and ultimately responsible for improving the quality of education received by students. The exercise of the teaching profession is full of intentionality and requires a deep knowledge of the dimensions that permeate the teaching and learning processes, namely, the human, technical and political-social dimensions. In this context, initial training is configured as a stage in the teacher training process that enables contact with different knowledge and discourses about education and pedagogical practice, guided by the National Curricular Guidelines for Higher Education Teacher Training (DCNs) and the Pedagogical Project of the Degree Course (PPC) where they study. At the same time, certain policies may contrast with the conception of education proposed by these documents, so that neoliberalism presents itself as an antagonistic political, social and economic model when looking at education from a market logic, neglecting its role in other spheres. Based on this, the This work aimed to collect the meanings of students completing undergraduate courses at the Federal University of São Carlos (UFSCar), Araras campus, regarding the role they attribute to the school together with their understanding of the teaching and learning processes, seeking to understand how such speeches and statements align or conflict with the DCNs and the neoliberal discourse. To this end, an online questionnaire and semi-structured interviews were used to capture the speeches that underwent subsequent discursive analysis, based on the Foucauldian framework, which sought identify in these speeches elements that highlight the construction of the subjectivity of these future educators in the context of initial teacher training, seeking to highlight the techniques of self and power responsible for modifying the experience that these individuals have of themselves and the world around them in these contexts. It was possible to verify the significant contribution of initial training in transforming the way in which undergraduates conceive the educational process and the role of the school and the teacher, in addition to revealing forms of resistance and opposition to the dominant discourse together with a deep knowledge and critical look at the challenges and the reality that the Brazilian educational scenario imposes, especially in relation to inequalities and school failure.
The constitution of teaching subjectivity: the confrontation between teacher training policies and the possible influences of neoliberalism
Keywords: Formação inicial; Initial formation; Subjetividade; Subjectivity; Neoliberalismo; Neoliberalism; Análise do Discurso; Speech analysis; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO